2022
DOI: 10.3389/fimmu.2022.749241
|View full text |Cite
|
Sign up to set email alerts
|

The Comprehensive Analysis Identified an Autophagy Signature for the Prognosis and the Immunotherapy Efficiency Prediction in Lung Adenocarcinoma

Abstract: BackgroundLung adenocarcinoma (LUAD) is a fatal malignancy in the world. Growing evidence demonstrated that autophagy-related genes regulated the immune cell infiltration and correlated with the prognosis of LUAD. However, the autophagy-based signature that can predict the prognosis and the efficiency of checkpoint immunotherapy in LUAD patients is yet to be discovered.MethodsWe used conventional autophagy-related genes to screen candidates for signature construction in TCGA cohort and 9 GEO datasets (tumor sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Many LUAD-associated prognostic models have been made available previously; for example, an immune-related prognostic signature constructed by Yi et al (2021) , a ferroptosis-associated prognostic signature introduced by Wang et al (2021) , an autophagy-related prognostic signature developed by Li et al (2022) , and an inflammatory-associated prognostic signature identified by Zhai et al (2021) have identified. Compared with these models, our study reported a prognostic model based on neddylation-associated genes which shows promising prognostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Many LUAD-associated prognostic models have been made available previously; for example, an immune-related prognostic signature constructed by Yi et al (2021) , a ferroptosis-associated prognostic signature introduced by Wang et al (2021) , an autophagy-related prognostic signature developed by Li et al (2022) , and an inflammatory-associated prognostic signature identified by Zhai et al (2021) have identified. Compared with these models, our study reported a prognostic model based on neddylation-associated genes which shows promising prognostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is of great significance to identify and characterize phagocytosis regulatory factors and clarify their roles in LUAD prognosis and immunotherapy response for the prognosis and treatment of LUAD patients. Gene signature is a biological function model constructed from the expression data of multiple genes, which can be used to predict the prognosis and progression of many types of malignant tumors (17). Yi et al constructed a prognostic model of 17-immune-related genes signature to predict survival and response to ICI (immune checkpoint inhibitors) in LUAD patients and the result showed that patients with a lowrisk score had a better prognosis and predicted benefit from ICI treatment (18).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is of great significance to identify and characterize phagocytosis regulatory factors and clarify their roles in LUAD prognosis and immunotherapy response for the prognosis and treatment of LUAD patients. Gene signature is a biological function model constructed from the expression data of multiple genes, which can be used to predict the prognosis and progression of many types of malignant tumors ( 17 ). Yi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, how to evaluate the efficacy of ICP therapy is a problem faced by the majority of oncologists (59)(60)(61). On the one hand, "magic drugs" will bring a resurrection effect to some patients, but on the other hand, improper use is likely to cause various side effects (62).…”
Section: Discussionmentioning
confidence: 99%